Legal Protection for Debtors in Online Loan Transactions in the Fintech Era - Amada, Fanesa; Kelik Wardiono (Universitas Semarang, 2025)
The rapid expansion of financial technology (fintech) lending has widened public access to credit, yet it has also intensified legal concerns related to unequal bargaining power, non-transparent contractual terms, and the vulnerability of specific debtor groups. This study analyzes the legal relationship formed in online loan agreements between student borrowers of UIN Raden Mas Said Surakarta and fintech lending providers, and examines the forms of legal protection available to them. Previous research has primarily focused on regulatory frameworks, leaving a gap in understanding how online loan contracts operate in practice among students as a uniquely vulnerable debtor group. Using a normative juridical method supported by a descriptive qualitative approach, this study employs statutory, conceptual, and case-based analyses, complemented by interviews with student users of peer-to-peer lending services. The findings show that online loan agreements formally meet the validity requirements under Articles 1320 and 1754 of the Civil Code and are legally recognized as electronic contracts under the Electronic Information and Transactions Law. However, the contracts are largely standardized, creating an imbalance of bargaining power that limits student autonomy and increases exposure to high-interest fees, data misuse, and one-sided clauses. Legal protection for debtors is provided through preventive mechanisms—including transparency obligations, personal data safeguards, and financial literacy initiatives—and repressive mechanisms such as civil remedies, OJK complaint processes, and alternative dispute resolution through LAPS SJK. Despite this framework, implementation remains weak due to limited legal awareness and suboptimal fintech supervision. The novelty of this study lies in its contextual analysis of student borrowers, revealing specific contractual vulnerabilities and proposing stronger regulatory enforcement and legal literacy strategies to ensure fair, transparent, and sustainable fintech lending practices.